2019
DOI: 10.1096/fj.201802017r
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G dimer targets Granzyme B pathway to prolong human renal allograft survival

Abstract: Human leukocyte antigen G (HLA‐G), a nonclassic HLA class Ib molecule involved in the maintenance of maternal tolerance to semiallogeneic fetal tissues during pregnancy, has emerged as a potential therapeutic target to control allograft rejection. We demonstrate here that the level of soluble HLA‐G dimer was higher in a group of 90 patients with a functioning renal allograft compared with 40 patients who rejected (RJ) their transplants. The HLA‐G dimer level was not affected by demographic status. One of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…48,49 In experimental models and by cell culture experiments it was shown that application of soluble HLA-G dimers inhibits activation of CD8 + T cells and downregulates granzyme B expression by binding to ILT2. 59 Soluble HLA-G in a dimerized form inhibits T cell responses, which suggests that it directly triggers ILT2. 60 ILT2 may also prevent efficient T cell activation: it is thought that ILT2 modulates CD8 + T cell activation by blocking the binding of HLA class I to CD8.…”
Section: Does Pregnancy Failure Results From Maternal T Cells Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 In experimental models and by cell culture experiments it was shown that application of soluble HLA-G dimers inhibits activation of CD8 + T cells and downregulates granzyme B expression by binding to ILT2. 59 Soluble HLA-G in a dimerized form inhibits T cell responses, which suggests that it directly triggers ILT2. 60 ILT2 may also prevent efficient T cell activation: it is thought that ILT2 modulates CD8 + T cell activation by blocking the binding of HLA class I to CD8.…”
Section: Does Pregnancy Failure Results From Maternal T Cells Attackmentioning
confidence: 99%
“…Decidual CD8 + EM T cells express significantly lower perforin and granzyme B levels compared with their peripheral blood counterparts 48,49 . In experimental models and by cell culture experiments it was shown that application of soluble HLA‐G dimers inhibits activation of CD8 + T cells and downregulates granzyme B expression by binding to ILT2 59 . Soluble HLA‐G in a dimerized form inhibits T cell responses, which suggests that it directly triggers ILT2 60 .…”
Section: Maternal T Cells and Myeloid Cells In The Placental Bedmentioning
confidence: 99%
“…In addition, being an in vivo model, we avoided artificial culture conditions and growth factors essential for in vitro assays, allowing for a more dynamic and natural background for an allogeneic immune response. The NSG mouse used in this model has defective VDJ recombination and a mutation in the IL-2R gamma chain, allowing for maximal engraftment of human immune cells and making it the most amenable strain for studying allogeneic immune responses (20,(60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 81 healthy individuals vs 82 renal transplant recipients, a SNP in LILRB1 (rs1061680) has been shown to associate with increased carotid intimal media thickness (192) but additional comprehensive studies evaluating LILRB1 expression or genetic variation in kidney transplantation are lacking. By comparing 90 patients with a functional renal allograft and 40 patients rejecting their transplant, Ajith et al confirmed the protective effect of high levels of the soluble HLA-G dimers (193). They also studied the underlying mechanism by genomic-and cellular analysis of patient derived T cells and in LILRB1 transgenic mouse models.…”
Section: Hla-g As Immune Checkpoint For Nk Cells Expressing Kir2dl4 And/or Lilrb1mentioning
confidence: 98%